Sustainability Level of Management of â€œPondok Dadapâ€ Fish Auction Place to Support Marketing of Marine Fish in Sendangbiru, East Java - Zainal Abidin; Mimit Primyastanto (Wacana Journal of Social and Humanity Studies, 2017)
This research aims to analyze the level of sustainability management of fish auction place (TPI) Pondok Dadap. Methods of data analysis using the techniques of Multidimensional Scalling (MDS) through a RAPFISH approach. The results showed that the average index value of sustainability management of fish auction place (TPI) "Pondoddadap" of 61, its meaning is quite sustainable. Sustainability index value of each dimension, i.e. the ecological dimension of 62.41%, economic dimension of 66.51%, social dimension of 23.68%, institutional dimension of 76.13%, and infrastructure dimension of 76.27%. The recommended factors to improve the status of sustainability are the availability of places of waste disposal activities TPI or waste treatment installations, an increasing number of fish traders in TPI, keeping the potential conflicts between fishermen and traders so that does not happen, the availability of human resources that support the auction, keeping the role of KUD in the auction, as well as the availability of garbage disposal.